PERAN MODERNISATOR DALAM MEWUJUDKAN KABUPATEN LAYAK ANAK DI KOLAKA - Mardiana; Sarwan Amin; Murni Ratna Sari Alaudin (Halu Oleo University, 2023)
Violence against children has increased since 2020 in Kolaka Regency, resulting in the safety of children being threatened. For this reason, research was carried out at the Women's Empowerment and Child Protection Service (DP3A) a government institution whose role is to protect children in Kolaka Regency. This study used a qualitative descriptive analysis by conducting observations and interviews with DP3A employees, the Head of the Kolaka District Children's Forum, the KLA task force, and the community. The research findings show that the government is a stabilizer by issuing regulations that are oriented towards tackling child violence and a modernizer that initiates various programs while at the same time collaborating with government agencies, NGOs, SKPD, and the community in various forms of socialization and training activities related to reporting, prevention, and protection of children's rights. DP3A has attempted to enhance its role as a modernizer to protect children and to make Kolaka a Child-Friendly District. This becomes a reference for the government to find formulations that can help minimize acts of violence against children in Indonesia.